Optimal design and evaluation of a photovoltaic water pumping system - حسين سامر; علي أحمد محمود; علي بديع خضور (Latakia University Journal -Engineering Sciences Series, 2023)
Water pumping systems using photovoltaic panels are one of the most promising and important applications, as these systems help in protecting the environment and reduce emissions compared to systems that use diesel generators. This research studies the use of a photovoltaic-powered water pumping system and the research shows technical, economic and environmental studies that compare photovoltaic and diesel pumping solutions. The kwh cost of a PV pumping system is (0.149) ⁄ kwh, while the kwh cost of a diesel pump system is (0.304) ⁄ kwh.